Experimental Investigation on Flow Boiling and Pressure Drop of R1233zd (E) in Cold Plate with Parallel Channels - Wang Yuchen; Fang Yidong; Su Lin; Yang Wenliang; Zhang Zhao (Zhileng xuebao)
As a critical component of two-phase cooling systems, the pressure drop characteristics of refrigerants in cold plates with parallel channels significantly affect their heat-transfer performance. In this study, experiments are conducted to investigate the frictional pressure drop of low-pressure refrigerant R1233zd(E) in a cold plate under different mass fluxes (118–1 300 kg/(m2 s)) and inlet subcooling temperatures (2–8 K). The single-phase and two-phase frictional pressure drops of the refrigerant are analyzed simultaneously with the vapor and liquid velocity characteristics. The results show that for the single-phase refrigerant, the frictional pressure drop in the channel first decreases and then increases as the heat flux increases. When the refrigerant enters the two-phase state, the frictional pressure drop increases rapidly with the heat flux. As the mass flux increases, bubble nucleation and an abrupt increase in the frictional pressure drop are delayed. In addition, both the liquid velocity and the slip ratio increase with the heat flux. At the same outlet vapor quality, a higher slip ratio is observed at higher mass fluxes, which results in a more significant increase in the frictional pressure drop.